2008
DOI: 10.1534/genetics.108.094318
|View full text |Cite
|
Sign up to set email alerts
|

Insulator and Ovo Proteins Determine the Frequency and Specificity of Insertion of the gypsy Retrotransposon in Drosophila melanogaster

Abstract: The gypsy retrovirus of Drosophila is quite unique among retroviruses in that it shows a strong preference for integration into specific sites in the genome. In particular, gypsy integrates with a frequency of .10% into the regulatory region of the ovo gene. We have used in vivo transgenic assays to dissect the role of Ovo proteins and the gypsy insulator during the process of gypsy site-specific integration. Here we show that DNA containing binding sites for the Ovo protein is required to promote site-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…We have also used antibodies against histone H3 tri-methylated at lysine 27 (H3K27me3), a histone posttranslational modification linked to transcriptional repression (Cao et al 2002;Plath et al 2003;Sarma et al 2008), as well as antibodies against histone modifications H3 acetylated at lysine 9 (H3K9ac), H3 acetylated at lysine 14 (H3K14ac), and H3 tri-methylated at lysine 4 (H3K4me3), which are normally associated with transcriptional activation (Barski et al 2007;Jenuwein and Allis 2001;Ng et al 2003;Santos-Rosa et al 2002;Wang et al 2008). In addition, we have also used H3 mono-methylated at lysine 27 (H3K27me1), which was previously identified because of its association with heterochromatin but also with DAPI bands as well as with active transcription (Barski et al 2007;Labrador et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…We have also used antibodies against histone H3 tri-methylated at lysine 27 (H3K27me3), a histone posttranslational modification linked to transcriptional repression (Cao et al 2002;Plath et al 2003;Sarma et al 2008), as well as antibodies against histone modifications H3 acetylated at lysine 9 (H3K9ac), H3 acetylated at lysine 14 (H3K14ac), and H3 tri-methylated at lysine 4 (H3K4me3), which are normally associated with transcriptional activation (Barski et al 2007;Jenuwein and Allis 2001;Ng et al 2003;Santos-Rosa et al 2002;Wang et al 2008). In addition, we have also used H3 mono-methylated at lysine 27 (H3K27me1), which was previously identified because of its association with heterochromatin but also with DAPI bands as well as with active transcription (Barski et al 2007;Labrador et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Labrador et al (2008) found that distal enhancers could bypass two these insulators only when they were inserted in opposite orientations. These authors supposed that some additional sequences in the gypsy retrotransposon (provirus) form a stem-loop structure allowing this bypass, which is only possible when the two gypsy copies are in the opposite (but not the same) orientations.…”
Section: Discussionmentioning
confidence: 99%
“…However, gypsy transposons — LTR retrotransposons that are active in D. melanogaster — often insert into the ovo locus. Endogenous gypsy mobilization can thus be visualized when an endogenous gypsy transposon inserts into engineered ovo sequences, which results in the activation of a GFP reporter 21,27 . This approach has revealed that somatic gypsy insertions occur in aged D. melanogaster neurons 21 .…”
Section: Introduction To Mobile Elementsmentioning
confidence: 99%